Pelatihan Desain Pembelajaran Teaching Factory Kompetensi Keahlian Teknik Permesinan - Bahri, Syamsul; Siraj, Siraj; Fatwa, Islami; Jumadi, Jumadi; Alfiady, Teuku (Aceh Journal of Community Engagement (AJCE), 2024)
One of the biggest challenges in vocational education is the gap between the skills taught in schools and the actual needs in the industry. *Teaching Factory* provides a solution by integrating industrial processes and technologies directly into the curriculum. The implementation mechanism of this community service program is carried out through stages of needs analysis, partnership offers with industry partners, activity execution, and activity evaluation. The results achieved have successfully improved teachers' ability to design and implement more applicable and industry-relevant learning. Although there were some challenges faced, particularly in terms of limited facilities, this activity has had a significant impact on the quality of learning and the readiness of students to work in the industry